Dietary inclusion of Orange peels derived pectin and Lactobacillus plantarum for Nile tilapia (Oreochromis niloticus)cultured under indoor biofloc systems - Hien Van Doan (2019)
© 2019 Elsevier B.V. A 12-week feeding trial was carried out to investigate possible effects of dietary orange peels derived pectin (OPDP)and Lactobacillus plantarum CR1T5 (LP)singularly or combined on innate immune response, disease resistance, and growth performance of Nile tilapia fingerlings under indoor biofloc system. The fingerlings were fed the following diets: diet 1 (0 g kg−1 OPDP and 0 CFU g−1 L. plantarum), diet 2 (10 g kg−1 OPDP), diet 3 (108 CFU g−1 L. plantarum), and diet 4 (10 g kg−1 OPDP +108 CFU g−1 L. plantarum). At the end of feeding trial, skin mucus parameters, serum immune parameters, and growth performance were measured. Ten randomly selected fish were used in a challenge test with Streptococcus agalactiae. The results indicated that supplementations of OPDP + LP or/and significantly (P <.05)increased growth performance, skin mucus and serum immunity responses. The highest values were revealed in fish fed both OPDP and LP vs. individual applications. However, no significant (P >.05)differences were observed between fish fed OPDP and LP. The challenge test revealed that the relative percent survival (RSP)in diet 2, diet 3, and diet 4 was 43.33%, 50.0%, and 70.0%, respectively. Among the supplemented groups, fish fed 10 g kg−1 OPDP + LP showed significant (P <.05)higher RPS and resistance to S. agalactiae than the other groups. The present results suggested that the combination of OPDP and LP could be considered as potential feed-additives for aquaculture farmed fish under indoor biofloc system.